2022
DOI: 10.1057/s41599-022-01371-6
|View full text |Cite
|
Sign up to set email alerts
|

Single motherhood in Ghana: analysis of trends and predictors using demographic and health survey data

Abstract: The rising rate of single-mother families has gained scholarly and policy attention. Understanding the dynamics in the socio-economic and demographic transformations that have led to the relatively high single-mother families in Ghana is important to advance policy and intervention to mitigate adverse effects of single motherhood. The study sought to examine the trends and predictors of single motherhood in Ghana from 1993 to 2014. This paper was based on data from the last five waves of the Ghana Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The hierarchical nature of the Demographic and Health Survey (DHS), which involves respondents being layered within survey clusters, has the potential to bias standard errors. Therefore, the Huber-White technique was utilised to derive robust standard errors, as suggested by Ayebeng, et al [ 23 ]. A multicollinearity test was performed on each variable, and the results indicated that the variables in the models had a mean-variance inflation factor (VIF) of 2.34.…”
Section: Methodsmentioning
confidence: 99%
“…The hierarchical nature of the Demographic and Health Survey (DHS), which involves respondents being layered within survey clusters, has the potential to bias standard errors. Therefore, the Huber-White technique was utilised to derive robust standard errors, as suggested by Ayebeng, et al [ 23 ]. A multicollinearity test was performed on each variable, and the results indicated that the variables in the models had a mean-variance inflation factor (VIF) of 2.34.…”
Section: Methodsmentioning
confidence: 99%
“…Among single mothers, economic equilibrium variables, such as household earnings and housing type, had a more substantial impact on depression (Kim, 2018). Therefore, there is a correlation between single mothers' poverty and a greater rate of depressive symptoms (Atkins (2010); Ayebeng et al, (2022); Montoya (2017); Babaiefard (2014); Chant (2014)).…”
Section: Economic Insufficiencymentioning
confidence: 99%
“…Multiple risk factors often cluster together in adverse environments. For example, poverty often co‐occurs with other factors such as single parenthood, residential instability, and crowding in LMICs (Ayebeng et al., 2022; Barbarin & Richter, 1999; Walker et al., 2011). Research conducted predominantly in Western and other high‐income countries has shown that the cumulative effect of these risk factors on adjustment is more detrimental than the impact of each individual risk exposure (Evans et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Families in sub‐Saharan West Africa, especially in Ghana, disproportionately experience numerous contextual risk factors that affect them. These factors, such as poverty, hunger, large family size, and single parenthood, have been linked to adverse psychosocial outcomes among adolescents (Ayebeng et al., 2022; Black et al., 2017; Grantham‐McGregor et al., 2007; Greif & Dodoo, 2015; Walker et al., 2007). Despite the relevance of the cumulative risk approach in the Ghanaian context, only a few studies have investigated the combined effect of multiple risks on adjustment outcomes.…”
Section: Introductionmentioning
confidence: 99%